1997
DOI: 10.1016/s0091-6749(97)70221-5
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to indoor allergens in early infancy and sensitization

Abstract: Background: Indoor allergens play a major role both in sensitization and as triggers of asthma in children. The relationship between allergen exposure and sensitization to cats, dogs, and mites was studied prospectively in 100 newborn babies with a history of allergy in both parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
62
1
4

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 27 publications
8
62
1
4
Order By: Relevance
“…4,5 The absence of a dose-response association in children with an atopic mother might be explained by the fact that in children with a positive family history of allergy, low levels of allergen exposure might already be sufficient to cause sensitization. 4,7,8 In our study we did not observe an association between mite allergen exposure and persistent wheeze. This is in accordance with the results of others.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…4,5 The absence of a dose-response association in children with an atopic mother might be explained by the fact that in children with a positive family history of allergy, low levels of allergen exposure might already be sufficient to cause sensitization. 4,7,8 In our study we did not observe an association between mite allergen exposure and persistent wheeze. This is in accordance with the results of others.…”
Section: Discussioncontrasting
confidence: 77%
“…6 Other studies showed no relationship between mite, cat, or dog allergen exposure and the development of sensitization. 7,8 With respect to asthma, Sporik et al 9 reported that exposure to high levels of mite allergens in early childhood was associated with an increased risk of asthma at 11 years of age. However, these results were not confirmed by later studies in children up to 7 years of age.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study in the USA showed an inverse U-shape association between cat exposure and sensitization (1852). There are also studies reporting no association between cat allergen exposure and sensitization (1853,1854). Methodological challenges need to be addressed in these studies.…”
Section: Early Exposure Of Petsmentioning
confidence: 99%
“…알레르기 질환을 일으키는 주된 실내 환경요인으 로는 집먼지진드기, 고양이, 개, 바퀴벌레 등이 있으 며 (Beltrani, 2003;Eggleston et al, 1998;Munir et al, 1997), 이러한 실내 알레르기 항원이 많을수록 알레 르기 질환 발병에 시너지 효과를 일으킨다고 보고하 고 있다 (Chen et al, 2003).…”
unclassified